Writing lichen. - Marsh, Rachel; Hughes, Briony (Resurgence & Ecologist)
The article focuses on Clare Goulet's poetry collection, particularly her exploration of lichens through a multifaceted lens that combines poetry, amateur lichenology, and historical context. Goulet's work emphasizes the symbiotic nature of lichens, which consist of fungi and photosynthesizing organisms, and challenges traditional metaphors used in scientific discourse. The article highlights the complexity of understanding lichens, suggesting that they embody both organism and ecosystem, and encourages readers to appreciate the interplay of science and poetry in Goulet's writing. Three sections from her poem "Graphis scripta" are included, showcasing her innovative approach to metaphor and the richness of lichen as a subject.